Living in the mountains. Late Mesolithic/early Neolithic settlement in northwest Portugal: Rock Shelter 1 of Vale de Cerdeira (Vieira do Minho) - Xavier, Pedro (2022)
In the 1990s, a research project was developed to identify, in the mountainous areas of the Northwest (NW) of Portugal, the existence of an occupation model associated with the last hunter–gatherer prehistoric communities in the region. Therefore, a set of consistent and detailed field surveys took place in the mountains of NW Portugal, leading to the discovery of the archaeological site named “Rock Shelter 1 of Cerdeira Valley,” a granite rock shelter situated in Cabreira mountain. The campaigns of excavations undertaken permitted the identification of two combustion structures, from which charcoal samples provided two C-14 dates, as well as a significant stone tool assemblage (around 30,000 pieces), that established the prehistoric occupation of “Rock Shelter 1 of Cerdeira Valley” between the Late Mesolithic and the Early Neolithic. This archaeological site and its body of evidences are being analysed within the context of an ongoing PhD project developed by one of the authors (P. Xavier), through two mutually related lines of research. The first one relates to the complete technological and typological study of the lithic assembly, identifying the objectives of the stone tool production, i.e. lithic production systems and related châines opératoires; and the second concerns itself with the classification and characterisation of different raw materials exploited by the prehistoric communities and, wherever possible, to make some additional considerations about raw material procurement. The goals of this article are the presentation of the methodologies adopted in the study of raw materials and the results obtained from the techno-typological study